Health Literacy and Social Determinants: Insights from Marginalized Contexts - Lilimadani, Maharnum Pramitya (Yayasan Sinergi Kawula Muda, 2025)
Health literacy is a critical determinant of health outcomes, particularly for marginalized communities facing systemic inequities and cultural barriers. This narrative review aimed to synthesize existing literature on health literacy in marginalized populations, focusing on barriers, strategies, and global comparisons. Literature was retrieved from Scopus, PubMed, and Google Scholar, yielding 58 studies that met the inclusion criteria and were analyzed in this review”. Inclusion criteria encompassed peer-reviewed studies published between 2010 and 2025 addressing conceptual, empirical, or intervention-based perspectives on health literacy. Both qualitative and quantitative studies were analyzed through thematic synthesis. The results indicate that marginalized groups consistently experience barriers related to educational attainment, cultural and linguistic misalignment, and digital inequities, leading to diminished preventive care and poorer health outcomes. Community-led initiatives, culturally tailored health communication, and trusted messengers emerged as effective strategies to mitigate these barriers, fostering greater engagement and trust. Comparative evidence further highlighted disparities between high-income and low- and middle-income countries, with successful models of intervention demonstrating adaptability across different contexts. The discussion emphasized the influence of systemic factors such as policy design, socioeconomic instability, and educational inequities, underscoring the need for integrated and context-specific approaches. This review concludes that addressing health literacy among marginalized populations requires policy reforms, digital innovation, and community-driven strategies to ensure sustainable progress. Future research should prioritize longitudinal, mixed-methods studies and expand representation to under-researched groups to strengthen the evidence base for effective interventions.